The Extent of Use of Concrete-Representational-Abstract (CRA) Model in Mathematics - Toong, Nelsa Gallo- (International Journal For Research In Mathematics And Statistics, 2020)
This study aimed to determine the extent of use of CRA model in Mathematics. The schools covered by this study were the 5 secondary schools in the Division of Negros Occidental of School Year 2015 – 2016. There were 267 Grade 8 students who were taken as respondents of the study. The study was descriptive and correlational in nature. The research utilized mean, weighted mean and Pearson Product- Moment Coefficient of Correlation. The study revealed that the extent of teachers’ use of CRA model in addition and subtraction of integers, multiplication and division of integers, polynomials, linear equations in one unknown, factoring, addition of rational numbers, algebraic word problem and angles as perceived by the students was “high”. Likewise, the study further revealed that the academic performance of more or less one-fourth of the students in Mathematics was in the “developing” level.